Biosynthesis of monensins A and B: the role of isoleucine - Pospísil, S; Sedmera, P; Krumphanzl, V; Vanĕk, Z (Folia microbiologica, 1986)
Isoleucine added to the cultivation medium of Streptomyces cinnamonensis C-100-5 induced a relative increase of the production of monensin B at the expense of monensin A. U-14C-Isoleucine was found not to be a specific monensin B precursor. The incorporation of 1-13C-2-methylbutyrate into monensins A and B showed the label to be evenly incorporated in both products at carbon atoms originating from C(1) of propionate. In regulatory mutants insensitive to 2-amino-3-chlorobutyrate isoleucine influenced the production of monensins only slightly but strains resistant to 2-aminobutyrate and norleucine decreased their total production by 2-12% in the presence of isoleucine which was associated with a decrease of monensin A content by 14-52%. The inhibitory effect of isoleucine on the biosynthesis of valine, a specific precursor of the butyrate unit of monensin A, is discussed.
Keywords: norleucin; furany; Aminobutyrates; Furans; Monensin; mutace; Norleucine; Valine; Isoleucine; Mutation; aminobutyráty; valin; Butyrates; monensin; butyráty; isoleucin; Streptomyces